2010
DOI: 10.1111/j.1462-2920.2010.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

High temporal and inter‐individual variation detected in the human ileal microbiota

Abstract: The diversity and temporal stability of the predominant bacteria in the human ileum was studied with the use of ileal effluent samples of seven individuals with Brooke ileostomies. The total number of bacteria within the ileal effluent was in the range of 10⁷ -10⁸ bacteria per gram (wet weight). The diversity of the bacteria in the ileal effluent showed marked differences compared with that in faecal samples from age-matched healthy adults. The ileal effluent had a higher relative abundance of species within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
239
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(268 citation statements)
references
References 52 publications
25
239
1
3
Order By: Relevance
“…), Clostridium clusters IX (Veillonella sp.) and XIVa (several genera), and several Gamma Proteobacteria, thereby displaying higher similarity with microbiota composition profiles obtained from ileostoma effluent samples (Booijink et al, 2010), which was supported by cluster analysis (Figure 1a). Principle component analysis analysis suggested that ileostomy effluent cluster closely to the jejunal sample, whereas the terminal ileum samples were more similar to feces as explained by 48% of the data along the first principle component (Figure 1b).…”
Section: Small Intestine Versus Ileostomysupporting
confidence: 50%
See 3 more Smart Citations
“…), Clostridium clusters IX (Veillonella sp.) and XIVa (several genera), and several Gamma Proteobacteria, thereby displaying higher similarity with microbiota composition profiles obtained from ileostoma effluent samples (Booijink et al, 2010), which was supported by cluster analysis (Figure 1a). Principle component analysis analysis suggested that ileostomy effluent cluster closely to the jejunal sample, whereas the terminal ileum samples were more similar to feces as explained by 48% of the data along the first principle component (Figure 1b).…”
Section: Small Intestine Versus Ileostomysupporting
confidence: 50%
“…Hierarchical clustering of probe profiles was carried out using the Euclidian distance and Ward's minimum variance method. These small intestinal microbiota composition profiles generated for the samples obtained from healthy subjects were compared with the ileostoma effluent profiles that were already present in the database (Booijink et al, 2010). Multivariate statistical software Canoco 4.5 for windows (Leps and Smilauer, 2003;Biometrix, Plant Research International, Wageningen, The Netherlands) was used to perform the principle component analysis on log-transformed HITChip probe signal-intensity profiles.…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. aureus, principal representante dos microrganismos gram-positivos, é componente da microbiota normal e está presente na pele e nas narinas de aproximadamente um terço da população (PEACOCKET et al, 2001;NULENS et al, 2005;GORWITZ et al, 2008). E. faecalis e E. faecium também fazem parte da microbiota do trato gastrintestinal humano (BOOIJINK et al, 2010) e, assim como S. aureus, são típicos patógenos oportunistas que causam diversas infecções (WILLEMS et al, 2011).…”
Section: Fundamentação Teóricaunclassified